Role of the Sigma-1 receptor in Amyotrophic Lateral Sclerosis (ALS) - Timur A. Mavlyutov; Lian-Wang Guo; Miles L. Epstein; Arnold E. Ruoho (Elsevier, 2015)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease affecting spinal cord motoneurons (MN) with an associative connection to Frontotemporal Lobar Dementia (FTLD). The endoplasmic reticulum (ER) bound Sigma-1 Receptor (S1R) chaperone protein localizes to specialized ER cisternae within 10 nm of the plasma membrane in spinal cord ventral horn cholinergic post synaptic C-terminals. Removal of the S1R gene in the Superoxide Dismutase-1 (SOD-1) mouse model of ALS exacerbated the neurodegenerative condition and resulted in a significantly reduced longevity when compared to the SOD-1/S1R wild type (WT) mouse. The proposed amelioration of the ALS phenotype by the S1R is likely due to a "brake" on excitation of the MN as evidenced by a reduction in action potential generation in the MN of the WT when compared to the S1R KO mouse MN. Although the precise signal transduction pathway(s) regulated by the S1R in the MN has/have not been elucidated at present, it is likely that direct or indirect functional interactions occur between the S1R in the ER cisternae with voltage gated potassium channels and/or with muscarinic M2 receptor signaling in the post synaptic plasma membrane. Possible mechanisms for regulation of MN excitability by S1R are discussed.